Outline of a logic of knowledge of acquaintance. (2nd June 2018) - Iaquinto, Samuele; Spolaore, Giuseppe
Abstract: The verb 'to know' can be used both in ascriptions of propositional knowledge (e.g. 'Mary knows that Smith smokes') and ascriptions of knowledge of acquaintance (e.g. 'Mary knows Smith'). In the formal epistemology literature, the former use of 'know' has attracted considerable attention, while the latter is typically (dis)regarded as derivative. This attitude may be unsatisfactory for those philosophers who, like Russell, are not willing to think of knowledge of acquaintance as a subsidiary or dependent kind of knowledge. In this paper we outline a logic of knowledge of acquaintance in which ascriptions like 'Mary knows Smith' are regarded as formally interesting in their own right, remaining neutral on their relation to ascriptions of propositional knowledge. The resulting logical framework, which is based on Hintikka's modal approach to epistemic logic, provides a fresh perspective on various issues and notions at play in the philosophical debate on acquaintance.